Objetivos y consecuencias del mandato 8 y su reglamento - Riofrío Luciano, Luis Felipe (2010)
The Mandate 08, was issued by the Constituent Assembly, with the goal of eliminating the practices precarious recruitment, which had abused workers, for in this way achieve social justice. Therefore several institutions were deleted the legal system, in order to fulfill the objective cited above, creating in turn other Institutions that filled the vacuum existing legal and generate in turn decent working conditions. However this would be the emblem under which is promulgated the Mandate 08, which was the subject of a number of criticism, it is necessary to carry out an objective analysis that would allow forming a criterion.